2018
DOI: 10.7150/thno.25798
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced autophagy contributes to protective effects of IL-22 against acetaminophen-induced liver injury

Abstract: Acute or acute-on-chronic liver failure is a leading cause of death in liver diseases without effective treatment. Interleukin-22 (IL-22) is currently in clinical trials for the treatment of severe alcoholic hepatitis, but the underlying mechanisms remain to be explored. Autophagy plays a critical role in alleviating liver injury. The aim of the current study is to explore the role of autophagy in IL-22-mediated hepato-protective effect against acetaminophen (APAP)-induced liver injury.Methods: A model of acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 54 publications
1
37
0
Order By: Relevance
“…In this study, we found APAP stimulated the ATG family ( Figure 3E). Several studies, within the context of APAP-induced autophagy, have indicated the possibility that APAP may inhibit mTOR activity and decrease cellular ATP levels to trigger AMPK activation (Ni et al, 2013;Mo et al, 2018). Therefore, we speculate that APAP activates the AMPK pathway and regulate the ATG family (Bordi et al, 2019;Xing et al, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…In this study, we found APAP stimulated the ATG family ( Figure 3E). Several studies, within the context of APAP-induced autophagy, have indicated the possibility that APAP may inhibit mTOR activity and decrease cellular ATP levels to trigger AMPK activation (Ni et al, 2013;Mo et al, 2018). Therefore, we speculate that APAP activates the AMPK pathway and regulate the ATG family (Bordi et al, 2019;Xing et al, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…Of note, AMPK, a vital energy sensor, regulates cell metabolism to sustain organism homeostasis [35]. Particularly, AMPK also prevents cell or tissue damage by alleviating mitochondrial dysfunction and inhibiting cell apoptosis [36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, therapeutic targeting of these metabolic processes in hepatocytes therefore can be directly favorable to the prevention or treatment of liver injury diseases. Finally, with recombinant IL-22 proteins at present being explored as potential therapeutic strategies in human diseases as severe alcoholic hepatitis, graft-versus-host disease and inflammatory bowel disease, our research may have momentous clinical significances [18][19]37].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the relationship between Th22 cells and clinical disease has attracted increased attention. IL‐22 protects against multiple infections of the lungs and intestine as well as liver injury, but it also has pathogenic roles in rheumatoid arthritis and psoriasis . However, few studies have investigated the roles of Th22 cells and IL‐22 in AS.…”
Section: Introductionmentioning
confidence: 99%
“…IL-22 protects against multiple infections of the lungs and intestine as well as liver injury, but it also has pathogenic roles in rheumatoid arthritis and psoriasis. [29][30][31][32][33] However, few studies have investigated the roles of Th22 cells and IL-22 in AS. Our previous study revealed significant increases in the peripheral Th22 cell numbers and IL-22 levels of patients with acute coronary syndrome (ACS) compared to patients with stable angina pectoris (SAP) and control patients, suggesting that the circulating Th22-type response may have a potential role in the onset of ACS symptoms.…”
Section: Introductionmentioning
confidence: 99%